PREDICCIÓN DE LA ESTRUCTURA Y CARACTERÍSTICAS BIOQUÍMICAS DE LA ACETATO TIOQUINASA - Tovar, Jairo A.; Bioquímica Computacional y Estructural, Departamento de Bioquímica y Nutrición Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2013)
The activities of the enzymes implied in the metabolism of the ketonic bodies are present in neurons, like in astrocytes and in oligodendroglia. The use of prirnary cell cultures has shown that these ketonic bodies can be metabolized in these cells. The acetate tiokinase reported in having in neural cells, is an enzyme that reduces the energy cost of the use of the acetate significantly and therefore it intends like an election route in metabolism of this substance. The prediction data for biochernical and structural properties of the enzyme show a stable structure, with segments conserved between al! the existent sequences and a high structural flexibility, characteristic of most of the enzymes.